Identifikasi Hambatan Belajar Siswa Kelas X Madrasah Aliyah Negeri 1 Pekanbaru Pada Topik Trigonometri - Fauziah Fauziah (Lembaga Anotero Scientific Pekanbaru, 2022)
The purpose of study was to identifying student’s learning obstacle of Trigonometry by using student’s worksheet.This research is descriptive analysis research. This research was conducted in class X Madrasah Aliyah Negeri 1 Pekanbaru with a total of 30 students. The students worksheet (LKS) provided contains two learning activities. In first activity, students in groups were asked to find the rules of trigonometric formulas and use them in solving problems. Futhermore, in second activity students were asked to work on practice questions based on the rules of the Trigonometry formulas they discussed in the previous activity. Data collection were carried out based on student’s answerson the LKS. Furthermore, the student’s answer were analyzed to indentifying student’s learning obstacle on the topic of Trigonometry. Based on results of the analysis of student answers, it can be seen that most students are wrong in using the concept of the cosine rule because the are wrong determining the front side and the side flanking the angle and are unable to know the formula that must be used to solve the problem. Based on the result of this study, it can be seen that the use of student’s worksheets (LKS) is effevtive in identifying student learning obstacle, especially on topic of Trigonomentry so that they can be followed up in the next learning process.